2015
DOI: 10.1890/14-1332.1
|View full text |Cite
|
Sign up to set email alerts
|

Invasive toads shift predator–prey densities in animal communities by removing top predators

Abstract: Although invasive species can have substantial impacts on animal communities, cases of invasive species facilitating native species by removing their predators have rarely been demonstrated across vertebrate trophic linkages. The predictable spread of the invasive cane toad (Rhinella marina), however, offered a unique opportunity to quantify cascading effects. In northern Australia, three species of predatory monitor lizards suffered severe population declines due to toad-induced lethal toxic ingestion (yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“…Direct population level impacts of cane toads have not been restricted to a single goanna species but a multitude of native predators in terrestrial and aquatic ecosystems including other monitor lizards, crocodiles, snakes and quolls (Shine 2010;. Doody et al (2006Doody et al ( , 2009Doody et al ( , 2013Doody et al ( , 2015 demonstrated that cane toad-induced decline of goannas can have cascading effects on species not predicted to be directly affected by cane toads such as small lizards, tree snakes, freshwater turtles and grain-eating birds in riparian systems in northern Australia. Cane toads have also been reported to have direct suppressive effects on their invertebrate prey, and to compete with nesting birds for burrows (Boland 2004;Greenlees et al 2007;.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Direct population level impacts of cane toads have not been restricted to a single goanna species but a multitude of native predators in terrestrial and aquatic ecosystems including other monitor lizards, crocodiles, snakes and quolls (Shine 2010;. Doody et al (2006Doody et al ( , 2009Doody et al ( , 2013Doody et al ( , 2015 demonstrated that cane toad-induced decline of goannas can have cascading effects on species not predicted to be directly affected by cane toads such as small lizards, tree snakes, freshwater turtles and grain-eating birds in riparian systems in northern Australia. Cane toads have also been reported to have direct suppressive effects on their invertebrate prey, and to compete with nesting birds for burrows (Boland 2004;Greenlees et al 2007;.…”
Section: Discussionmentioning
confidence: 99%
“…Given the extent of their reported direct impacts, we contend that it is likely that cane toads have also had indirect impacts on species which have strong interactions with species that have declined following the toad invasion. Indeed, given the multitude of possible indirect interaction pathways they could potentially disrupt (Doody et al 2009(Doody et al , 2013(Doody et al , 2015, we suspect that the invasion of cane toads has affected a much greater range of taxa than has thus far been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guild members are characterized as generalist, opportunistic predators possessing a degree of dietary overlap (Losos & Greene, 1988; Shine, 1986). The spread of the invasive cane toad ( Rhinella marinas ) has decreased populations of many varanid species across northern Australia (Doody et al., 2009; Doody, James, et al., 2014; Doody, Mayes, et al., 2014; Doody et al., 2017; Doody, Soanes, et al., 2015; Shine, 2010), potentially changing the nature of these guilds.…”
Section: Introductionmentioning
confidence: 99%